Conventicles: Organising Dissent in Restoration Scotland. (December 2020) - McIntyre, Neil
Abstract : This article uncovers the dynamics of presbyterian conventicling after the Restoration settlement of 1661–2. In contrast to traditional accounts that have tended to foreground the exploits of dissenting clergy and especially itinerant preachers, particular attention is paid to the participation and organisational strategies of lay activists. It is argued that conventicles were formidable not only as sites of alternative worship, but as a well-organised and highly politicised opposition to Restoration governance that was genuinely popular in nature.